(untitled) (Itinerarios Educativos, 2024)
This article exposes the final report of the degree thesis that was carried out within the framework of the Bachelor’s Degree in Educational Sciences with an orientation in Politics and Government of Education, which is taught at the Faculty of Educational Sciences of the University Nacional de Entre Ríos, and whose defense was carried out in mid-2023. The complexity of these times demands reflection on what the school teaches, why and how it teaches it. Given the scarce production on the articulation between interdisciplinarity and primary school in Argentina, through this research -which was carried out in 2022- we sought to recognize and understand the teacher representations around interdisciplinary work in primary school. From the conduct of semi-structured interviews with teachers of a state-run school institution in the city of Vera (Province of Santa Fe) in 2022, an attempt was made to modify the meanings that those who teach interdisciplinarity give it, paying special attention to the implementation of the Interdisciplinary Content Cores, a curricular document published in 2016 in the Province of Santa Fe, as an initiative of the Ministry of Education.